Contribution to the Chinese subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae: Rhaphidophorinae) IV: Seven new species of Rhaphidophora and one new mitogenome - Lu, Xiangyi; Liu, Jing; Huang, Xiaojuan; Bian, Xun (Zootaxa, 2022)
Seven new species and the female sex of Rhaphidophora xishuang Gorochov, 2012 of the rhaphidophorines are described from China. The images illustrating the morphology of the two known species are provided. Meanwhile, the complete mitogenome of Rhaphidophora quadrispina was assembled. The mitogenome was 15892 bp in length and contained the typical gene arrangement. All examined specimens are deposited in the Guangxi Normal University.